Strategi Guru Pendidikan Agama Islam Sebagai Upaya Mengatasi Perilaku Bullying Siswa (Studi Kasus di SMP Negeri 1 Peterongan Jombang) - Dewi Anggraeni; Lailaturrohmah Selan; Laily Masruroh (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the world of modern education, this educational process in practice also has several obstacles that affect the quality of the education. One branch of juvenile delinquency is the issue of bullying. For this reason, this research raises and examines the factors that can cause this suffering as well as several strategies used by teaching staff, especially Islamic teachers at SMP Negeri 1 Peterongan Jombang. The consequences of this review are as per the following: Types of harassment behavior found include mocking or making friends with inappropriate names, seriously mocking friends, spitting at friends, making friends angry by hitting them first. the existence of peer groups that encourage or influence bullying behavior.